Review of The Literature, Prospects, and The Impact of Bancassurance on The Stability of The Banking Industry - Anita Hakim Nasution; Lukmandono Lukmandono (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
Existing literature, as well as empirical studies on Bancassurance, emphasize that there has been a shifting business in the bank from selling bank products to IKNB (Non-Bank Financial Industry). In this study, Bancassurance is one of the IKNBs that must be sold because the feather-based income is quite large and has a small risk because the bank is a referral as a distribution agent. The purpose of this research is to determine the characteristics of Bancassurance in various countries for the first time in Indonesia so that our human resources are not unfamiliar with the insurance sold in banks and can adjust the strategy to market characteristics in Indonesia. This paper discusses Bancassurance with various methodologies ranging from Expert Judgment to Risk Management by involving 15 international journal studies related to the implementation of Bancassurance in various countries including Google Scholar, Elsevier, and Science Direct. This paper will be useful as a topic for further research where researchers can identify the effect of bancassurance on banking, risks that occur in bancassurance practice, solutions to sales strategies, and system bottlenecks that occur between bank sales and sales bancassurance. The result of this research is the reluctance of selling banks to sell insurance products because they do not understand the concept of life insurance and unit link. In addition, bancassurance sales resources placed in the bank are not as good as insurance agents in general due to different incentives, incentive problems, and bottlenecks in the sales execution flow also make insurance targets cannot be achieved optimally. The solution is that Re-skills must be done in the "Virtual Century" era because the insurance link unit has also shifted from offline meetings to online so that all systems are done digitally. Coordination between resources is expected to go through a digitization process so that customer claims are quickly resolved, referrals are quickly executed and periodic coaching can be carried out by prohibited branch heads/superiors. Bancassurance with unit link customization/personalization will be a new value proposition.